Derivatives of alpha-phosphorylated aldehydes - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Conditions for the selective chlorination of a-phosphorylated aldehydes as a means of synthesising alpha-monochloro- and alpha,alpha-dichlorosubstituted derivatives are described. Dichloro derivatives show high reactivity and easily add thiols, amides and ethyleneimine to give stable hemi-thioacetals, hemiamidals and hemiaminal. From the silyl ether of hemiisopropyl thioacetal above 140 degrees C,alpha-ketophosphonate is obtained by the elimination of silane followed by the rearrangement of the oxirane intermediate. Alkylations of a-phosphorylated aldehydes with alkyl bromides gave enol ethers, However, dihalogenoalkanes such as 1,2-dibromoethane or 1,3-dibromopropane yielded phosphatecyclanes along with enol ethers, all in trans configuration, (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: phosphonous aldehydes and derivatives; phosphorus heterocycles; alkylation